TYPOGRAPHY INSPIRATIONS IN 21st - CENTURY: SOCIAL AND CULTURAL ROLES OF MODERNIST BAUHAUS IN GRAPHIC DESIGN - Stephen T.F. Poon, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
A critical examination of the historical, political, social and cultural significance of Bauhaus social and cultural impacts is presented in this paper, with a focus on Modernist typography’s social and cultural relevance today. Design literature shows that Bauhaus-inspired experimental forms of “new” typefaces and letterforms, initially perceived as avant-garde due primarily to its abstract conformity to sharpness and uniformity, gained eminence as the 20th-century progressed, and eventually preferred over traditional type-forms and widely applied to business publications to enhance readability and legibility. Many designers today acknowledge that Bauhaus typefaces have transformed graphic design and typesetting practices through its clarity of visual communication properties which promotes modernity and adaptability to social, technological and cultural trends. This paper analyses the typographic forms and innovations used in modern graphic designs, logos, advertising and brand literature which validate the importance of visual typefaces to improve recognisability and credibility. Through case studies, this paper contributes critical perspectives to type design research by demonstrating that regardless of usage and application, Bauhaus-inspired typographic imageries, letterforms, and logos continue to be relevant in improving visual communication logic, order and clarity, enabling fuller social interaction and cultural exchange by ensuring legibility and visual consistency.